ETHNOGRAPHER B. KH. KARMISHEVA'S INTERPRETATION OF THE ETHNIC DESCRIPTION OF THE SMALL NUMBER OF NATIONS IN THE SURKHAN OASIS - Turaev Sherzod Gulboy ugli (Journal of Learning on History and Social Sciences, 2024)
In this article, the ethnically small population living in the Surkhan oasis at the beginning of the 20th century is analyzed. This group included Turkmens, Gypsies, Iranians, Arabs, Kyrgyz and Jews. Also, the origin, division into groups, locations and economic activities of these peoples are highlighted. In the creation of the article, researches of ethnographer B.Kh. Karmisheva were mainly used.